Tinjauan Kebijakan pada Rencana Aksi Nasional Eliminasi Kanker Leher Rahim sebagai Pencegahan Primer Kanker Serviks di Indonesia: Perspektif Vaksinasi HPV berdasarkan Rekomendasi Pusat Pengendalian dan Pencegahan Penyakit: Tinjauan Pustaka - Kusuma, Fitriyadi; Suryoadji, Kemal Akbar (Cermin Dunia Kedokteran, 2026)
Introduction: Cervical cancer is the second most prevalent cancer among women in Indonesia and ranks third globally. It accounts for 7.5% of cancer-related deaths worldwide, with a notable impact in developing nations like Indonesia. The primary cause is high-risk Human Papillomavirus (HPV); however, the risk can be lowered through vaccination. This review aims to evaluate Indonesia's policy for implementing a national HPV vaccination program targeting school-aged children and assess its conformity with CDC guidelines. Methods: The study involved an extensive review of literature, as well as international and Indonesian policy documents. Results: The CDC recommends HPV vaccination for individuals aged 9-26, ideally beginning at 11 or 12 years old. In line with this, Indonesia has included the HPV vaccine in its national immunization schedule. The Indonesian Ministry of Health intends to require HPV vaccination for school-aged children, aiming for full national implementation by 2023. This reflects Indonesia's strong commitment to a comprehensive cervical cancer prevention strategy. The policy's alignment with CDC recommendations emphasizes the country's dedication to primary prevention through HPV vaccination. Conclusion: By enforcing HPV vaccination for school-aged children, Indonesia aims to substantially decrease the incidence and mortality rates associated with cervical cancer. This policy represents a significant advance in the fight against cervical cancer in Indonesia and could serve as a model for other countries contending with similar public health issues.